2017
DOI: 10.1186/s12879-017-2676-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV-DNA and inflammatory markers in HIV-infected individuals with different viral load patterns

Abstract: Background: Persistent residual viremia (RV) and low grade inflammation and immune activation have been associated with non-AIDS defining events. The impact of persistent RV and HIV-DNA load on immune activation/ inflammation remains unclear. The purpose of this study was to gain new insights into the relation between viremia, markers of inflammation and HIV-DNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…However, the correlations between such markers and the degree of viral suppression have not been thoroughly explored. Two studies observed no association between LLV and CRP levels , whereas conflicting results regarding sCD14 levels have been reported . We hypothesized that LLV could trigger persistent inflammation and coagulation cascades and that this in turn may contribute to progression of atherosclerosis in PLHIV.…”
Section: Introductionmentioning
confidence: 89%
“…However, the correlations between such markers and the degree of viral suppression have not been thoroughly explored. Two studies observed no association between LLV and CRP levels , whereas conflicting results regarding sCD14 levels have been reported . We hypothesized that LLV could trigger persistent inflammation and coagulation cascades and that this in turn may contribute to progression of atherosclerosis in PLHIV.…”
Section: Introductionmentioning
confidence: 89%
“…Blood and faecal samples were collected from each subject included in the study and submitted to the quantitative measurements of CD4+ T-lymphocytes and viral load [26], and to the microscopic observation of the wet smears stained with Lugol, directly or after Ridley concentration [27], respectively. Genomic DNA was then extracted from stool samples and submitted to PCR amplification using primers previously described [28], which target a fragment of about 600 bp from the Blastocystis -SSU rRNA gene, following PCR protocol and conditions described in Mattiucci et al, 2016 [13].…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have looked for correlations between markers of immune activation and HIV RNA level in virological responders, with inconsistent results. Some studies have reported links between, for example, markers of inflammation (TNF α , IL‐6), of monocyte activation (soluble CD14) or T cell activation (HLA‐DR, CD38), as well as exhaustion (PD‐1) on one hand, and viral load on the other hand. Yet, other studies did not observe these correlations .…”
Section: The Issue Of Inflammation and Immune Activationmentioning
confidence: 99%